PENGARUH MASA PAKAI DAN TINGKAT TRANSMISI TERHADAP KADAR EMISI GAS BUANG SEPEDA MOTOR HONDA ASTREA GRAND - I Made Adi Sayoga (Universitas Mataram, 2011)
Recently reducing emissions of the harmful gases that generated in the combustion process of the automobile and other internal combustion engine is absolutely essential to environmental preservation. These emissions pollute the environment and contribute to the global warming, acid rain, smog, odours, and respiratory and other health problems. Therefore many countries around the world are taking major efforts to toughen emission standards. Motor cycles, the lagers amount, contributed the major air pollution in Indonesia. The hamful gases that generated in the motor cycles especially CO, HC and NOx . As the motor cycles is getting older, many components in the combustion system are getting worst and contribute more hamfull emissions. This research was done on July 2001 to find out the emissions and was done on Honda Astrea Grand which have been used since 1995, 1996 dan 1997 on the variety of gear level. A multigas analyser was used to analyse the emission gas out form the tile pipe. The result shows that the maximum CO and HC emission are generated by all motor cycle on the first gear. The higerst CO and HC emission is generated by the olderst motor cycle (1995) and the minimum CO and HC emission is generated by the motor cycle that has been used since 1997.